Revered and reviled: a sentiment analysis of female and male referents in three languages - Levshina, Natalia; Koptjevskaja-Tamm, Maria; Östling, Robert (Frontiers in Communication, 2024)
Our study will contribute to the less explored domain of lexical typology, focusing on semantic prosody and connotation. "Semantic derogation", or pejoration of nouns referring to women, whereby such words acquire connotations and further denotations of social pejoration, immorality and/or loose sexuality, has been a very prominent diachronic question in studies on gender and language (change). It has been argued that pejoration emerges due to the general derogatory attitudes towards female referents. However, the evidence for systematic differences in connotations of female-vs. male-related words is fragmentary and often fairly impressionistic; moreover, many researchers argue that the sentiment towards women (as well as men) is often ambivalent. One can also expect that the gender differences in connotations have decreased over the recent years, thanks to feminism and social progress. We test these ideas in a study of positive and negative connotations of feminine and masculine terms in pairs like woman -man, girl -boy, wife -husband, etc. Sentences containing these words were sampled from diachronic corpora of English, Chinese and Russian, and sentiment scores for every word were obtained using two systems for Aspect-Based Sentiment Analysis: PyABSA, and OpenAI's large language model GPT-3.5. The Generalised Linear Mixed Models of our data provide no indications of significantly more negative sentiment towards female referents in comparison with their male counterparts, although some of the models suggest that female referents less often have neutral sentiment than male ones. Our data also do not support the hypothesis of the diachronic convergence between the genders. These results suggest that pejoration is unlikely to be explained by overall more negative attitudes to female referents.